2006
DOI: 10.1016/j.pain.2006.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Parental catastrophizing about their child’s pain. The parent version of the Pain Catastrophizing Scale (PCS-P): A preliminary validation

Abstract: Numerous studies have found evidence for the role of catastrophizing about pain in adjustment to pain in both adults and children. However, the social context influencing pain and pain behaviour has been largely ignored. Especially in understanding the complexities of childhood pain, family processes may be of major importance. In line with the crucial role of pain catastrophizing in explaining adjustment and disability in adults and children, this study investigates the role of parental catastrophic thinking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
325
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 289 publications
(343 citation statements)
references
References 30 publications
11
325
7
Order By: Relevance
“…In terms of parental distress, the present findings suggest that contextual threat may play a more important role than the overall tendency of parents to endorse catastrophic thought about child pain. At first sight, these findings stand in contrast with prior research highlighting pain catastrophizing as an important construct in understanding parental responses [36,39]. However, our findings corroborate recent evidence 20" " showing that the specific level of threat persons attach to a situation has higher predictive value in explaining their response to pain than their general tendency to interpret pain as threatening (i.e., catastrophizing) [11,12].…”
Section: " "contrasting
confidence: 59%
See 2 more Smart Citations
“…In terms of parental distress, the present findings suggest that contextual threat may play a more important role than the overall tendency of parents to endorse catastrophic thought about child pain. At first sight, these findings stand in contrast with prior research highlighting pain catastrophizing as an important construct in understanding parental responses [36,39]. However, our findings corroborate recent evidence 20" " showing that the specific level of threat persons attach to a situation has higher predictive value in explaining their response to pain than their general tendency to interpret pain as threatening (i.e., catastrophizing) [11,12].…”
Section: " "contrasting
confidence: 59%
“…The PCS-P yields a total score that can range from 0 to 52, and three subscale scores for rumination, magnification and helplessness. The PCS-P has been shown to be reliable and valid [36]. The Cronbach's alpha in this study was α = .89.…”
Section: Parental Catastrophizing About Their Child's Painmentioning
confidence: 51%
See 1 more Smart Citation
“…Specifically, individuals catastrophizing about their pain report more pain and distress 68,70 . Likewise, observers catastrophizing about other's pain seem to experience another's painful situation as more distressing 33,36,52 . Other individual difference variables may reduce fear and distress.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, evidence in parents of school children has also shown that parents with high levels of catastrophizing are more likely to infer higher levels of pain in their child (Goubert, Vervoort, Cano, & Crombez, 2009), and more likely to be distressed or fearful about their child's pain (Caes, Vervoort, Eccleston, & Goubert, 2011;Goubert, Vervoort, Sullivan, Verhoeven, & Crombez, 2008). Accordingly, it is reasonable to assume that parents' catastrophizing about their child's pain, by means of associated behavioural parental responses, might also promote fear and pain in their child (Goubert, Eccleston, Vervoort, Jordan, & Crombez, 2006). To date, evidence on the impact of parents' catastrophizing upon the child's response to pain is limited.…”
mentioning
confidence: 99%